Physical Education and Sports - Gošnik, Jelka; Tuđa, Andrija (2004)
Physical Education and sports have formed an important part of the Faculty of Philosophy's activities and development ever since it was founded. The leading figure in the promotion of sports and Physical Education in Croatia Franjo Bučar not only initiated a number of sports disciplines, but also introducted Physical Education classes. Physical Education was slow to penetrate the University's curricula - the Faculty of Philosophy being no exception. Between the two World Wars, efforts were redoubled to introduce Physical Education intro the University's curricula, but also as a field of study. In 1948, Physical Education entered the Faculty of Philosophy with a flourish. Students regularly compete in all kind of sport competitions, the University one and also the Faculty.
ENG